Investigation on the dead reckoning of autonomous robotic vehicle - Tan, Tor Hee. (2008)
This project is to demonstrate the use of a method for improving the accuracy in dead-reckoning error from its destination point and develop algorithms for navigation on a small microprocessor-controlled robotic vehicle moving from a starting point to a required destination under the guidance of a reflective tape within a defined environment.